Coenzyme Q10 and Cardiovascular Diseases - Francisco M. Gutierrez-Mariscal; Silvia de la Cruz-Ares; Jose D. Torres-Peña; Juan F. Alcalá-Diaz; Elena M. Yubero-Serrano; José López-Miranda (MDPI AG, 2021)
Coenzyme Q10 (CoQ10), which plays a key role in the electron transport chain by providing an adequate, efficient supply of energy, has another relevant function as an antioxidant, acting in mitochondria, other cell compartments, and plasma lipoproteins. CoQ10 deficiency is present in chronic and age-related diseases. In particular, in cardiovascular diseases (CVDs), there is a reduced bioavailability of CoQ10 since statins, one of the most common lipid-lowering drugs, inhibit the common pathway shared by CoQ10 endogenous biosynthesis and cholesterol biosynthesis. Different clinical trials have analyzed the effect of CoQ10 supplementation as a treatment to ameliorate these deficiencies in the context of CVDs. In this review, we focus on recent advances in CoQ10 supplementation and the clinical implications in the reduction of cardiovascular risk factors (such as lipid and lipoprotein levels, blood pressure, or endothelial function) as well as in a therapeutic approach for the reduction of the clinical complications of CVD.